Optimization of carbon dioxide laser cutting parameters - Muhammad Iqbal, Mohd Azit (2012)
This thesis presents the study of multi-optimization of carbon dioxide laser cutting process.There are many types of parameters involved in laser cutting which can be optimized in order to get the best quality output.In this study,three parameters are selected which are cutting speed, laser power frequency and its standoff distance to the workpiece.This thesis described how different sets of parameters can affect the result of laser cutting generated.The material chosen for this experiment is cast acrylic plastic glass.The range for cutting speed is 30mm/mm,40mmlmin and 50mm/mm.As for laser frequency variable,the levels are between 5 kHz,10 kHz and 15 kHz while a set of 30mm,60mm and 90mm are chosen for the standoff distance parameter.The theories show that higher value of each variable will generate smaller kerf width mark.From the analysis,it was found that the standoff distance proved to be the most significant influence to the result of kerf width produce.